The Youngest Reported and Successfully Treated Patient with a Dermoid Cyst of the Parotid Gland: A Rare Pediatric Case - Marcel Fabian Glaas; Jörg Schipper; Nelofar Kajasi; Angelika Albrecht (Case Reports in Otolaryngology)
Dermoid cysts (DCs) are rare benign, epithelial-lined lesions. Up to 7% of them are found in the head and neck region and 80% of those predominantly occur in the orbit, in the nose, and in the floor of the mouth. The average age of presentation is around the age of six. Dermoid cysts located in the parotid gland have only been published in 19 cases so far. Interestingly, the mean age of occurrence in the parotid gland was much higher (31 years). We report on a four-year-old girl being the youngest patient who had ever been diagnosed with this disease.